2017
DOI: 10.1002/hbm.23830
|View full text |Cite
|
Sign up to set email alerts
|

White matter integrity of central executive network correlates with enhanced brain reactivity to smoking cues

Abstract: The attentional bias to smoking cues contributes to smoking cue reactivity and cognitive declines underlines smoking behaviors, which were probably associated with the central executive network (CEN). However, little is known about the implication of the structural connectivity of the CEN in smoking cue reactivity and cognitive control impairments in smokers. In the present study, the white matter structural connectivity of the CEN was quantified in 35 smokers and 26 non-smokers using the diffusion tensor imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…White matter plays a vital role in regulating brain activity and the coupling between brain regions and behavioral regulation ( 29 ). Previous studies have found that the proportion of fiber bundles in the left striatum and hippocampus of insomnia patients reduced through DTI technology ( 30 ), which may mean the abnormal reduction of white matter fiber tracts in insomnia patients.…”
Section: Discussionmentioning
confidence: 99%
“…White matter plays a vital role in regulating brain activity and the coupling between brain regions and behavioral regulation ( 29 ). Previous studies have found that the proportion of fiber bundles in the left striatum and hippocampus of insomnia patients reduced through DTI technology ( 30 ), which may mean the abnormal reduction of white matter fiber tracts in insomnia patients.…”
Section: Discussionmentioning
confidence: 99%
“…White matter was notable in regulating brain activity and mediating the functional coupling between brain regions and behavior (Bi et al, 2017;Leong et al, 2016;Yuan et al, 2016). The volume of the white matter was currently mainly determined by voxel-based morphometry, which shows morphological changes of the white matter by calculating the volume and density of the white matter (Liu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact mechanism of nicotine addiction is still unknown, recent neuroimaging findings have advanced our understanding (4)(5)(6)(7)(8). Resting-state functional magnetic resonance imaging (rs-fMRI), measuring task-independent spontaneous brain activity in low-frequency blood oxygenation level dependent (BOLD) fluctuations (9), has been widely applied for delineating functional neural abnormalities in smokers (10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%